Adhesive formulation and particle size in making bio briquettes from bamboo pyrolysis waste charcoal raw material - Muhammad Heldita Agil Laresha; Devy Cendekia; Dewi Ermaya; Shintawati Shintawati; Adityas Agung Ramandani (Institution for Industrial Research and Standardization of Industry - Padang, 2024)
Bamboo is one of the biomass resources that Indonesia has a lot of untapped potential for using as a renewable energy source. Solid waste called biomass is used as a sustainable energy source to replace fossil fuels (i.e., petroleum), because it does not contain Sulphur and pollute the air. This study aimed to evaluate the quality of bio briquettes produced from waste charcoal from bamboo pyrolysis. being aware of the maximum calorific value depending on the adhesive quantity and particle size. Moreover, understand how the size of the particles and the amount of adhesive used impact the calorific value of bio briquettes. This study employed the pyrolysis of bamboo charcoal as its raw material. The charcoal's particle sizes varied, ranging from 30 to 50 mesh, and the percentage of tapioca adhesive varied from 6% to 10%, with a 1:10 adhesive to water ratio between the three samples. The results of the tests that have been carried out show that bamboo charcoal from bamboo pyrolysis can be used as bio briquettes of good quality. The highest calorific value was found in bio briquettes, with a variation in the percentage of adhesive of 6% and a particle size of 50 mesh, which was 6131.58 calories per gramme. The greater the percentage of adhesive used, the smaller the resulting calorific value, and the smaller the particle size used, the greater the resulting bio briquette calorific value.